Introduction: Paper from the conference: Neue Sachlichkeit, Political Music, or Vernacular Avant-Garde? Hanns Eisler and his Contemporaries - Fjeldsøe, Michael; Schweinhardt, Peter (Danish Yearbook of Musicology, 2019)